Results from a large post-marketing safety surveillance study in the Republic of Korea with a quadrivalent meningococcal CRM-conjugate vaccine in individuals aged 2 months–55 years - Byung Wook Yoo; Hye Lim Jung; Yoon Seob Byeon; Dong Ki Han; Nak Yeong Jeong; Carlo Curina; Luca Moraschini; Sung Jin Kim; Chiranjiwi Bhusal; Michele Pellegrini; Yan Miao (Human Vaccines & Immunotherapeutics, 2020)
The quadrivalent meningococcal conjugate vaccine MenACWY-CRM is approved in the Republic of Korea for use in individuals from 2 months of age. This single-arm, open-label, observational, multicenter, post-marketing study (NCT01766206) assessed the safety of MenACWY-CRM vaccine administered according to local clinical practice. A total of 3939 individuals aged 2 months–55 years provided safety data post-vaccination; the analysis was conducted on the per-protocol set (3920 participants). Solicited and unsolicited adverse events (AEs) were collected over 7 days post-vaccination and medically-attended AEs (MAAEs) and serious AEs (SAEs) over 29 days post-vaccination. Among recorded solicited AEs, injection site AEs were reported by 21.38% of participants, with tenderness/pain being most frequent across age groups; systemic AEs were reported in 13.95% of participants, with irritability (in ˂6-year-olds), headache and myalgia (in ≥6 year-olds) being the most frequently reported. Most solicited AEs were mild or moderate in nature. The percentage of participants reporting unsolicited AEs varied in the study population, i.e. 12.56% in participants aged 2–23 months and 3.18% in those ≥2 years of age. Overall, less than 22% of unsolicited AEs were considered as related to vaccination. MAAEs (10.89% of participants) were mostly mild; 2.82% were considered as related to vaccination. Three (0.46%) and 5 (0.15%) SAEs (none vaccination-related) occurred in participants aged 2–23 months and 2–55 years, respectively. No deaths were reported. The safety profile for MenACWY-CRM in this post-marketing surveillance was consistent with observations from studies conducted during the vaccine’s clinical development, with no new safety concerns.